Financial Constitution Issues in Development of the Basic Law for the Federal Republic of Germany in 1948-1949 - I. D. Popov (Научный диалог)
This   article   analyzes   the   key   problems of the financial constitution in the development of the Basic Law for the Federal Republic of Germany (FRG) in 1948-1949, based on materials from the Constitutional Convention at Herrenchiemsee and the Parliamentary Council of West Germany. It emphasizes that the relevance of this issue was influenced by Germany’s historical development, which had a long-standing experience in both regional and imperial financial administration. This led to high significance of financial constitution issues in post-war West German politics. It is concluded that the main approaches to this problem were developed at the Herrenchiemsee Convention in October 1948, and the main content of the financial section of the Basic Law was formulated in the financial committee at the beginning of October 1948. A key role in developing the financial constitution was played by parliamentarian H. HöpkerAschoff. However, until May 1949, the parties could not reach a consensus on matters of financial administration system and financial equalization. This was significantly influenced by constant objections from the occupying administrations, the position of the Christian Social Union in Bavaria (CSU), uncertainty in assessing financial conditions, and the Social Democrats’ consistent defense of broad financial powers for the federal center.